Preliminary Study on the In vitro and In vivo Effects of Asparagopsis taxiformis Bioactive Phycoderivates on Teleosts - Marino, Fabio; Di Caro, Gianfranco; Gugliandolo, Concetta; Spanò, Antonio; Faggio, Caterina; Genovese, Giuseppa; Morabito, Marina; Russo, Annamaria; Barreca, Davide; Fazio, Francesco; Santulli, Andrea (Frontiers in Physiology, 2016)
Several compounds from marine organisms have been studied for their potential use in aquaculture. Among the red algae, Asparagopsis taxiformis is considered one of the most promising species for the production of bioactive metabolites with numerous proposed applications. Here, the in vitro antibacterial activity, the easy handling and the absence of adverse effects on marine fish species are reported. Depending on the seasonal period of sampling, ethanol extracts of A. taxiformis exhibited significantly different inhibitory activity against fish pathogenic bacteria. The extract obtained in late spring showed strong antibacterial activity against Aeromonas salmonicida subsp. salmonicida, Vibrio alginolyticus, and V. vulnificus, and moderate activity against Photobacterium damselae subsp. damselae, P. damselae subsp. piscicida, V. harveyi and V. parahaemolyticus. Sea bass and gilthead sea bream were fed with pellets supplied with algae and algal extracts. The absence of undesired effects was demonstrated. Hematological and biochemical investigations allowed to confirm that the whole alga and its extracts could be proposed for a future application in aquaculture.